2014
DOI: 10.1186/1471-2377-14-87
|View full text |Cite
|
Sign up to set email alerts
|

NQO1gene rs1800566 variant is not associated with risk for multiple sclerosis

Abstract: BackgroundA possible role of oxidative stress in the pathogenesis of multiple sclerosis (MS) and in experimental autoimmune encephalomyelitis has been suggested. The detoxification enzyme NAD(P)H dehydrogenase, quinone 1 (NQO1) has been found up-regulated in MS lesions. A previous report described an association between the SNP rs1800566 in the NQO1 gene and the risk for MS in the Greek population. The aim of this study was to replicate a possible influence of the. SNP rs1800566 in the NQO1 gene in the risk fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
9
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 45 publications
0
9
2
Order By: Relevance
“…The methodology is similar to that used to detect other SNP allelic variants. 1 Hardy-Weinberg equilibrium was analyzed using DeFinetti software (http://ihg.gsf.de/cgi-bin/hw/hwa1.pl). The allelic and genotypic frequency analyses were performed using SPSS software, ver.…”
mentioning
confidence: 99%
“…The methodology is similar to that used to detect other SNP allelic variants. 1 Hardy-Weinberg equilibrium was analyzed using DeFinetti software (http://ihg.gsf.de/cgi-bin/hw/hwa1.pl). The allelic and genotypic frequency analyses were performed using SPSS software, ver.…”
mentioning
confidence: 99%
“…Along with Nrf2-HO1, NQO1 was increased in the brain as a protective mechanism against lead toxicity (Ye et al, 2016). To the contrary, Agúndez et al (2014) reported that the NQO1 gene does not show a significant correlation in comparison between MS patients and healthy controls. These inconsistent NQO1 results suggest the possibility of site-dependent differences in NQO1 expression or Nrf2independent changes in NQO1 expression in the spinal cord.…”
Section: Discussionmentioning
confidence: 99%
“…The study, which was conducted in accordance with the principles of the Helsinki declaration of 1975, was approved by the Ethics Committees of Clinical Investigation of the University Hospital “Príncipe de Asturias” (University of Alcalá, Alcalá de Henares, Madrid, Spain), the Infanta Cristina University Hospital (Badajoz, Spain), and Clínica Universitaria de Navarra (Pamplona, Spain). Most of the patients recruited had participated in other previous studies of genetic association with MS risk 1 24 25 26 27 28 29 30 .…”
Section: Methodsmentioning
confidence: 99%
“…Despite Genome-wide association studies (GWAS) in MS confirmed more than 100 loci with genome-wide significance (most of them with modest odds-ratio-OR), only HLA (in particular the HLA-DRB1*15:01 haplotype) showed a strong association with the risk for MS 1 . Many studies of oxidative stress markers in the brain, spinal cord, and cerebrospinal fluid of patients diagnosed with MS, and in the experimental model of autoimmune encephalomyelitis (EAE), suggested a possible role of oxidative stress and lipid peroxidation in the pathogenesis of MS (revised in 1 ).…”
mentioning
confidence: 99%
See 1 more Smart Citation